2004
DOI: 10.1128/aem.70.1.255-261.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Population Dynamics of Xanthomonas axonopodis pv. manihotis in Colombia from 1995 to 1999

Abstract: Restriction fragment length polymorphisms (RFLPs) were used to study the population genetics and temporal dynamics of the cassava bacterial pathogen Xanthomonas axonopodis pv. manihotis. The population dynamics were addressed by comparing samples collected from 1995 to 1999 from six locations, spanning four different edaphoclimatic zones (ECZs). Forty-five different X. axonopodis pv. manihotis RFLP types or haplotypes were identified between 1995 and 1999. High genetic diversity of the X. axonopodis pv. maniho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…Although a lower number of clearly scorable bands were observed in some isolates (Figure 5), the three repeats of rep-PCR amplifications revealed that the absent bands are reproducible. The findings from the present study are in agreement with reports by Restrepo et al [33] demonstrating the high discriminatory power of rep-PCR when characterizing Xam populations with low levels of genetic diversity in Colombia.…”
Section: Genetic Diversity Of Xam Isolates By Rep-pcr Genomic Fingerpsupporting
confidence: 93%
“…Although a lower number of clearly scorable bands were observed in some isolates (Figure 5), the three repeats of rep-PCR amplifications revealed that the absent bands are reproducible. The findings from the present study are in agreement with reports by Restrepo et al [33] demonstrating the high discriminatory power of rep-PCR when characterizing Xam populations with low levels of genetic diversity in Colombia.…”
Section: Genetic Diversity Of Xam Isolates By Rep-pcr Genomic Fingerpsupporting
confidence: 93%
“…If that were the case, one would expect locally adapted populations to be recalcitrant to introduction of less-fit genotypes from other regions. Because replacement of bacterial plant pathogen populations has been observed in crops (38), it is important to determine whether pathogen population replacement has occurred over time for diseases of perennial crops. The replacement of pathogen populations could, in the long term, lead to dissimilar disease control strategies, because distinct populations would differentially affect host crops (41).…”
mentioning
confidence: 99%
“…AFLP has proven to be useful for identifying bacterial strains at subgeneric level [5,10,11,14,15,17,18,20]. Although the results of AFLP fingerprinting are specific and show high resolution to differentiate bacterial strains at the subgeneric level, it is very clear that the efficacy of this method not only depends on the choice of a suitable restriction enzyme that cleaves the most stable site in the bacterial genome but also depends on application of suitable primer to amplify the unique fragment of bacterial genome which can differentiate one strain from the others.…”
Section: Resultsmentioning
confidence: 99%
“…manihotis from each other and also from other Xanthomonas strains. Restrepo et al [18] characterized genetic structure and population dynamics of X. axonopodis pv. manihotis in Colombia from 1995 to 1999 and identified 45 RFLP types or haplotypes.…”
Section: Introductionmentioning
confidence: 99%